2015
DOI: 10.1007/s12094-015-1368-x
|View full text |Cite
|
Sign up to set email alerts
|

Shorter hemodialysis duration is a risk factor for the recurrence of urothelial carcinoma of the bladder in patients on maintenance hemodialysis

Abstract: Preoperative shorter hemodialysis duration is a risk factor for the occurrence and recurrence of UC of the bladder in patients undergoing MHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The incidence of bladder cancer has gradually increased in recent years. There is a modestly effective clinical prognosis despite systemic therapy for bladder cancer that is characterised by progression, metastasis, recurrence and drug resistance [ 2 , 3 ]. Although a great deal of advanced research has contributed to the understanding of bladder cancer, molecular mechanisms involved in the pathogenesis and progression of this disease remain poorly understood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of bladder cancer has gradually increased in recent years. There is a modestly effective clinical prognosis despite systemic therapy for bladder cancer that is characterised by progression, metastasis, recurrence and drug resistance [ 2 , 3 ]. Although a great deal of advanced research has contributed to the understanding of bladder cancer, molecular mechanisms involved in the pathogenesis and progression of this disease remain poorly understood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the risk is considered to be progressively higher in patients with a longer duration of dialysis [4]. However, Liu et al [5] showed that the highest standardized incidence ratio of urothelial carcinoma of the bladder occurred in the first 3 years of hemodialysis and that the risk gradually declined with prolonged hemodialysis. Moreover, Ricci [6] reported a significantly lower incidence of metastases in patients on hemodialysis compared with those not on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the Medical Research Ethics Committee of the Beijing Manuscript to be reviewed were obtained from all participants. A total of 111 right-handed participants (age ≥ 18 years) were enrolled in this study, including patients with hemodialysis for at least six months (Liu et al 2016b;Yen et al 2009)…”
Section: Participantsmentioning
confidence: 99%